WHEN THE SENSES DRIVE LOYALTY: THE IMPACT OF MULTI-SENSORY MARKETING AND SERVICE QUALITY ON STORE REVISIT INTENTION (Contemporary Journal of Social Science Review, 2025)
This study aims to examine how visual stimuli, olfactory stimuli, haptic stimuli, and perceived service quality influence store revisit intention in the retail context, with a particular focus on the moderating role of prior store experience. To achieve customer loyalty and long-term profitability, it is essential for retailers to understand the factors that drive customers’ intentions to return. The research suggests that visual stimuli such as store design, layout, and color scheme significantly enhance a store’s attractiveness and desirability, while also enriching the shopping experience by evoking emotions and memories. Haptic stimuli, including product surfaces and store fixtures, reflect the tactile sensations shoppers’ experience. Perceived service quality plays a crucial role, influencing customers during the purchase process as well as through interactions with sales staff. The uniqueness of this study lies in its holistic approach, as it investigates multiple sensory factors and their impact on customers’ revisit intentions, alongside the moderating role of prior store experience. Using behavioral assessments and questionnaires with retail customers, the study explores the complex relationships between sensory stimuli, service quality, and revisit intention. The findings provide valuable insights for retail businesses, highlighting that enhancing sensory experiences and delivering high service quality can foster customer loyalty and strengthen competitiveness in the dynamic retail industry.